Combination chemotherapy with NAB®‐paclitaxel and capecitabine for patients with advanced biliary tract cancer (NAP‐CAPABIL Pilot Study). Issue 5 (28th June 2021) - Woodford, Rachel; Brungs, Daniel; Leighton, Carly; Grimison, Peter; Sjoquist, Katrin M.; Becker, Therese; Robinson, Samuel; Gebski, Val; Wilson, Kate; Chantrill, Lorraine; Aghmesheh, Morteza
Abstract: Background:  Advanced biliary tract cancer (ABTC) is a highly aggressive malignancy, with a 5‐year overall survival of < 10%. Although preliminary evidence suggests a role of targeted treatments or immunotherapy in a subset of patients, chemotherapy remains the standard second‐line treatment in the majority. We conducted a pilot study of second‐line chemotherapy with capecitabine and nab‐paclitaxel after failure of gemcitabine and platinum. Methods: Eligible patients had histologically proven, unresectable biliary tract cancer, which had progressed on a gemcitabine/platinum doublet. In this single‐arm, multicenter trial, all patients received capecitabine (825 mg/m 2 bd PO D1‐14 q21d) and nab‐paclitaxel (125 mg/m 2 IV D1, 8 q21d) until progression or unacceptable toxicity. The primary objective was feasibility of delivering the proposed regimen, with secondary objectives of disease control measures and QOL outcomes. Results: Ten patients were enrolled between 2015 and 2016 from four cancer centers in NSW. Treatment was generally well tolerated with grade III toxicities in five patients (including infection, cholangitis, obstruction, and intestinal perforation) and no grade IV toxicity. Median treatment duration was 4.3 months, with a disease control rate of 80% (8/10), and median progression‐free and overall survival of 5.7 and 12.1 months, respectively. Quality of life data and specimens for translational research have been collected. Conclusions: Our pilot study demonstrates that combination of capecitabine and nab‐paclitaxel is feasible as a second‐line treatment in ABTC. Adequate safety and promising early efficacy signals make further assessment of the combination in a formal phase II or III trial reasonable. Clinical trial information: ACTRN12615000504516. Abstract : This single arm, open label, multicentre pilot study demonstrates that combination of capecitabine and nab‐paclitaxel is feasible as a second‐line treatment in ABTC. Adequate safety and promising early efficacy signals make further assessment of the combination in a formal phase II or III trial reasonable.